2016
DOI: 10.1007/s10661-016-5149-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of groundwater quality in a rural community in North Central of Nigeria

Abstract: Evaluation of water quality of nine boreholes and three open hand-dug wells in a rural community in North Central Nigeria revealed relative abundance of cations Na > k > Ca > Mg > Zn > Pb and anions Cl(-) > PO4(2-) > SO4(2-) > NO3(-) in the boreholes and cations Ca > Na > K > Mg > Pb and anions NO3(-) > PO4(2-) > SO4(2-) > Cl(-) in the wells. The major contaminants exceeding SON and WHO permissible limits were NO3(-) , Mg, TH, pH and Mg, Pb, TH, pH and DO in the wells and boreholes, respectively. They are attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 65 publications
7
33
5
Order By: Relevance
“…The lower than permissible pH range obtained from the different water sources can be linked to the geological formation in the community (Sojobi, 2016). Similar findings of low pH values were obtained for groundwater sources of neighboring Isoko North Local Governmental Area communities by Owamah et al (2013).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The lower than permissible pH range obtained from the different water sources can be linked to the geological formation in the community (Sojobi, 2016). Similar findings of low pH values were obtained for groundwater sources of neighboring Isoko North Local Governmental Area communities by Owamah et al (2013).…”
Section: Resultssupporting
confidence: 75%
“…The need to regularly monitoring of the quality of groundwater used as drinking water in rural and suburban communities of developing countries cannot be over-emphasized (Owamah et al, 2013;Sojobi, 2016). This is because, inadequate access to potable water and unavailability of reliable information on quality are major contributors to frequent outbreak of pathogenic diseases in the region.…”
mentioning
confidence: 99%
“…Groundwater samples collected from 24 wells distributed throughout the heavily industrialized district of Kocaeli (Dilovasi), Turkey indicated that among other pollutants microbial pollution due to fecal contamination also exists (Yolcubal et al, 2016). Enterobacter aerogenes and E-coli (Sojobi, 2016).…”
Section: Microbial Contaminationmentioning
confidence: 99%
“…Groundwater samples collected from nine boreholes and three hand-dug wells in Omu Aran in North Central region of Nigeria, showed the presence of enterobacter aerogenes and E-coli indicating the possibility of human and animal feces contamination (Sojobi, 2016). The authors attributed the microbial pollution in Omu Aran to poorly managed boreholes that are vulnerable to the droppings from domesticated goats and sheeps, and due to the proximity of the borehole to the poorly designed septic tank systems and…”
Section: Microbial Contaminationmentioning
confidence: 99%
“…Water resources management is a crucial factor for humanity and other living creatures; however, achieving the optimal quality is possible only with proper management . Water resources management should be applied for many reasons, such as anthropogenic activities, and natural processes can deteriorate the water resources, such as rivers and dams.…”
Section: Introductionmentioning
confidence: 99%